Flood Disaster Control in Urban Watersheds Based on a Coupled Model-A Case Study of a Region in Guangzhou - ZHU Bifang; GAO Yanzhe; LAI Chengguang (Renmin Zhujiang)
Urban flood disasters have become one of the major disasters affecting urban development.Therefore,studying urban flood disasters is of great practical significance.Taking a region in Guangzhou as an example,this study constructs a coupled hydrodynamic model that comprehensively considers the rivers,the pipe network,and the surface under a holistic view of the watershed system to evaluate the effect before and after flood control measures.The results suggest the following conclusions:① The simulated risk points are basically consistent with those in the static flood risk map,indicating that the results of the constructed coupled model are reasonable.② Under the current conditions,the study area is exposed to a high flood risk in the case of a once-in-a-century rainstorm,and corresponding measures should therefore be taken urgently to mitigate the flood risk in this area.③ The implementation of reconstruction measures,such as pipe network reconstruction and pump station expansion,well alleviates the flood risk in the study area,indicating that the reconstruction scheme is reasonable.The reconstruction of the pump station at the Hengsha Chong Estuary effectively mitigates the waterlogging in downstream Hengsha Chong,which proves that approaching flood disaster control in the watershed from a holistic view of the watershed is more scientific and reasonable.